Conditional Correlations and Volatility Spillovers between Crude Oil and Stock Index Returns of Middle East Countries - Aimer, Nagmi M. Moftah (Scientific Research Publishing, Inc., 2016)
This paper reveals the conditional correlations and fluctuation spillovers between oil price shocks and stock markets indices in Middle East countries, over the period from March 2000 to March 2015, by using the BEKK-GARCH, DCC-GARCH models. The results show strong evidence of fluctuation spillovers between the price of WTI to all exporting and oil importing stock indexes. The results further show that the estimates of the conditional correlations are always significant. Time-varying correlations of crude oil and stock index do not differ from oil-exporter or oil-importer countries. Crude oil price shocks have a significant impact on the relationship between crude oil and stock indices in the world crisis periods. The extent of the influence stock market collapse in 2008 crisis on the correlation coefficients is much more important than those of the previous financial crises.
Keywords: 8. Economic growth; 1. No poverty